Borland C++ builder programmalastırıw tiliniń grafikalıq imkaniyatlarınan paydalanıw - Kalxanov, P.J; Orınbaev, A.A (SCIENCE and SOCIETY, 2022)
This article is written about working with graphics using classes, properties and functions of Borland C++ Builder components. Bor- land C++ Builder is a powerful visual object-oriented programming system that allows you to create various graphic shapes. C++ Builder can be used anywhere with the extended C++ language standard to enhance existing applications, improve performance, and provide a
Keywords: programming; C++ Builder; graphics; canvas; windows; picture; brush; font; pen; components